Echocardiographic evaluation of asymptomatic left ventricular diastolic dysfunction in type 2 diabetes mellitus - Jasmeen Chahal; Monica Arora; Vidhi Singla; Ravinder Garg; Divya Soin; Sumit Pal Singh Chawla; Manjeet Kaur; Sandeep Kumar (Al Ameen Medical College, 2018)
Background: Diabetes is a chronic metabolic disorder and is a fast growing global epidemic with widespread physical, mental, social and economical consequences. The first stage of diabetic cardiomyopathy is represented by left ventricular diastolic dysfunction (LVDD) with preserved systolic function in an asymptomatic individual. Objectives: To determine the prevalence of asymptomatic LVDD in type 2 diabetes mellitus (DM) patients and to study the relationship between LVDD and age, duration of diabetes and glycemic control. Methods: This was a prospective case control and observational hospital-based study conducted on 200 subjects, 100 cases of type 2 DM aged 35-65 years with duration of diabetes more than 5 years and 100 age- and sex-matched controls without diabetes. Transthoracic 2D echocardiography (ECHO) was performed on all the subjects to detect the presence of LVDD. The data was compiled and tabulated to explore the association between DM and its various components with LVDD. Chi square test was used to test the significance of association. Results: LVDD was more prevalent in the study group patients as compared to controls (74% versus 18%). Presence of LVDD showed positive correlation with duration of diabetes, glycosylated hemoglobin (HbA1C) and presence of albuminuria, and negative correlation with estimated glomerular filtration rate (eGFR). Conclusions: LVDD is quite prevalent in type 2 DM as compared to general population and is a marker of evolving heart disease among diabetics. Presence of LVDD in diabetics increases with duration of disease, poor glycemic control, presence of albuminuria and worsening of GFR. Early diagnosis and treatment of LVDD in diabetic patients may reduce cardiovascular morbidity by preventing future development of heart failure in these patients.